CONTENT ANALYSIS OF ENGLISH ASSESSMENT RUBRICS USED IN SENIOR HIGH SCHOOLS RELIABILITY, TRANSPARENCY, AND LEARNING OUTCOME ALIGNMENT - Mohd. Rafi Riyawi; Zulhiddah (SOSIOEDUKASI, 2025)
This study examines the quality of English assessment rubrics used in senior high schools through an in-depth qualitative content analysis focusing on three key dimensions: reliability, transparency, and alignment with learning outcomes. A total of 12 rubrics were collected from public and private schools and analyzed alongside semi-structured interviews with English teachers. The findings reveal substantial inconsistencies in rubric construction, with only a minority of rubrics demonstrating clearly differentiated performance descriptors. Most rubrics employ vague evaluative terms and lack operational indicators, reducing their usefulness in guiding both assessment and student learning. Alignment with the Merdeka Curriculum was also limited, as several rubrics did not fully represent mandated competencies such as logical reasoning, content organization, and coherence. Interview data further highlight systemic challenges, including limited teacher training, time constraints, and reliance on generic online rubrics. These issues collectively undermine rubric reliability and transparency, resulting in subjective scoring and misaligned evaluations. The study underscores the need for standardized rubric development guidelines, targeted professional development, and stronger institutional support to ensure high-quality assessment practices. The findings contribute to enhancing the integrity of English assessment and provide practical insights for teachers, schools, and policymakers committed to implementing curriculum-aligned, competency-based evaluation systems.